MURABAHAH BIL WAKALAH (KAJIAN TEORI DAN PENERAPANNYA PADA LEMBAGA KEUANGAN SYARIAH) - M Yusuf K; Nasrullah Bin Sapa; Abdi Wijaya (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
This article discusses murabahah bil wakalah in theoretical studies and its application in Islamic financial institutions. The purpose of this article is to elucidate one type of contract in contemporary Islamic jurisprudence, namely the murabahah bil wakalah contract, through theoretical aspects and its application in Islamic financial institutions. The research method employed is the library research method or literature review. The literature review is specifically focused on revealing information derived from scholarly texts, including books and relevant academic journals related to the discussed topic. The research findings indicate that the murabahah bil wakalah contract, from a contractual perspective, is a combination of the murabahah and wakalah contracts, serving as a solution in its implementation within Islamic financial institutions.